A case study: an analysis and interpretation of Taqī al-Dīn al-Subkī's (d.756/1355)legal evolution - Aldhfar, Mohammed (2020)
This thesis demonstrates that there is relationship between the development of Islamic law and the context in which it is applied. Utilising the writings of the fourteenth century Mamlūk jurist Taqī al-Dīn al-Subkī (d. 756/1355) as a case study, the thesis concludes that the scientific, cultural, and socio-political development of the Early Mamlūk Sultanate in his era contributed to the evolution of his legal positions. This study examines three legal cases demonstrating al-Subkī’s legal development: 1) the legal method for determining the beginning of the month of Dhū al-Ḥijja, 2) the legal ruling against non-Muslims who curse the Prophet Muḥammad, and 3) the legal preference of establishing more than one Friday prayer in one city. This thesis highlights the importance of considering and utilising social history in understanding the development of Islamic law and therefore proposes an integration of social history into the current madrasa curriculum.